Hubungan Penggunaan Aplikasi Pesan Antar Makanan Terhadap Risiko Obesitas Pada Mahasiswa Di Derah Jabodetabek: Hubungan Penggunaan Aplikasi Pesan Antar Makanan terhadap Risiko Obesitas pada Mahasiswa di Daerah Jabodetabek - Layalia, Nida; Stefani, Megah (Universitas Airlangga, 2023)
Background: The trend of using food delivery applications is currently popular with students because it makes it easier for them to get food. However, this can cause negative impacts such as changes in the variety, frequency, and amount of food consumed, thereby risking increasing the prevalence of obesity. Objectives: This research aims to analyze the relationship between the use of food delivery applications, consisting of the frequency of use and the type of food/drink purchased, and the risk of obesity among students in the Jabodetabek area. Methods: The research used a cross-sectional design with a sample of 73 students in the Jabodetabek area. A purposive sampling technique was employed. Data was collected through an online questionnaire containing respondent characteristics, application use, Food Frequency Questionnaire (FFQ), and risk of obesity. Results: The food delivery application most frequently used by students was GoFood (42.5%). The majority of students used food delivery applications 1 – 3 times/week (94.5%). Meanwhile, coffee (27.4%) was the type of food/drink most often purchased through the application by students. Tests of the relationship between types of food/drinks and the risk of obesity showed several significant results, including fried chicken (p=0.03), baso aci (p=0.036), ice cream (p=0.018), and coffee (p=0.004). However, the test of the relationship between domicile and pocket money and the type of application used showed that the results were not significant with p=0.399 and p=0.163 respectively. The frequency of use of food delivery applications on the risk of obesity also did not show significant results (p=0.206). Conclusions: Several types of food/drinks were related to the risk of obesity. Student residence and pocket money were not related to the type of application used, and the frequency of use of food delivery applications was also not related to the risk of obesity.